FROM PERSUASION TO PURCHASE: EXAMINING FEAR OF MISSING OUT (FOMO) AS A MEDIATOR IN INFLUENCER MARKETING - Wildan Alfarizi; Ratih Hasanah Sudradjat (Pena Cendekia Insani, 2025)
This study examines the role of social media influencers in shaping consumer behavior, specifically focusing on TikTok creator Niky Cu. We explore how persuasive communication, particularly through urgency and social proof, triggers the fear of missing out (FOMO) and influences purchase intentions. Data were collected through an online survey of 400 respondents exposed to the influencer’s content. Findings indicate that message quality and the influencer’s appeal significantly impact FOMO and purchase intention. The results highlight the importance of emotional urgency and social influence in digital marketing, which often drives impulsive buying behavior without thorough consideration.